Influence of Zones of Pre‐Existing Crustal Weakness on Strain Localization and Partitioning During Rifting: Insights From Analog Modeling Using High‐Resolution 3D Digital Image Correlation. Issue 10 (26th October 2021) - Osagiede, Edoseghe E.; Rosenau, Matthias; Rotevatn, Atle; Gawthorpe, Rob; Jackson, Christopher A‐L; Rudolf, Michael
Abstract: Pre‐existing crustal structures are known to influence rifting, but the factors controlling their influence remain poorly understood. We present results of digital image correlation that allows for the surface strain analysis of a series of analog rifting experiments designed to test the influence of the size, orientation, depth, and geometry of pre‐existing crustal weak zones on strain localization and partitioning. We apply distributed basal extension to crustal‐scale models consisting of a silicone weak zone embedded in a quartz sand layer. We vary the size and orientation (α‐angle) of the weak zone with respect to the extension direction, reduce the thickness of the sand layer to simulate a shallow weak zone, and vary the geometry of the weak zone. Our results show that at higher α‐angle (≥60°) both small‐scale and large‐scale weak zones localize strain into graben‐bounding (oblique‐) normal faults. At lower α‐angle (≤45°), small‐scale weak zones do not localize strain effectively, unless they are shallow. In most models, we observe diffuse, second‐order strike‐slip intra‐graben structures, which are conjugate and antithetic under orthogonal and oblique extension, respectively. Generally, the observed spectrum of rift faulting styles (from discrete fault planes to diffuse fault zones, from normal to oblique and strike‐slip) highlights the sensitivity of rift architecture to the orientation, size, depth, and geometry of pre‐existing weak zones. Our generic models are comparable to observations from many natural rift systems like the North Sea and East Africa, and thus have implications for understanding the role of structural inheritance in rift basins. Key Points: The interplay between the orientation, size, depth, and geometry of inherited weak zone dictates their influence on rifting style Oblique normal‐slip and strike‐slip displacements are important strain accommodating mechanisms during oblique rifting Under oblique extension, intra‐graben faults that are orthogonal to the extension direction, initiate as strike‐slip Riedel shears